Capability of dual-modality electrical tomography for gas-oil-water three-phase pipeline flow visualisation. (August 2018) - Wang, Qiang; Polansky, Jiri; Wang, Mi; Wei, Kent; Qiu, Changhua; Kenbar, Asaad; Millington, David
Abstract: Numerous dual-modality tomography systems have previously been studied for multiphase flow characterisation, however, the capability of the majority of these systems was only demonstrated under limited flow regime conditions, such as stratified flow and slug flow. This paper reports a dual-modality electrical tomography for visualisation of industrial-scale, horizontal gas-oil-water three-phase flows. Experimental conditions include water-to-liquid ratio (WLR) from 0% to 100% in parallel with gas volume fractions (GVF) from 0% to 100%, which produced a variety of flow patterns, typically stratified flow, slug flow, plug flow, bubbly flow, and annular flow. A commercial dual-modality electrical tomographic system was utilised to carry out the measurement. A threshold-based data fusion method was also deployed for the fusion of oil-continuous and water-continuous data to provide full three phase images. The tomography visualisation is validated against optical photographs derived from a high-speed video logger located one diameter upstream of the device. The results demonstrate that a subcomponent of the dual modality sensor, an electrical resistance tomography (ERT) system, is able to visualise water continuous flow with WLR higher than 40%, providing good agreement with previous reports. The remaining subcomponent, the electrical capacitance tomography (ECT) system, is able to provide stable measurement during WLR from 0% to 90%, which is far beyond initial expectations and previous findings. Mean concentrations measured with the dual-modality system reveal the potential capability of the tomography system for phase fraction measurement. The visualisation results with the advanced data fusion method and mean concentration measurement verify the capability of the system in the application of gas-oil-water flow characterisation.